Multibeam bathymetry raw data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV METEOR during cruise M65/2 - Krastel, Sebastian; Brüning, Markus; Felzenberg, Janice Ann; Geersen, Jacob; Urlaub, Morelia; Vogt, Thomas; Zühlsdorff, Lars (PANGAEA, 2025)
Raw bathymetry data were collected using the ship's own Atlas Hydrosweep DS2 multibeam echosounder during the RV METEOR cruise M65/2. The cruise took place between 2005-07-04 and 2005-07-26 (Dakar, Senegal - Las Palmas, Canary Islands). Bathymetry data were recorded along with sub-bottom (Parasound) profiling along all seismic profiles and transits between stations. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) data from the cruise are archived at the BSH, thus no SVP files are added to this dataset. Data are unprocessed and therefore can contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).
Keywords: Bathymetry; Multibeam Echosounder